The parasitic fly Nemorilla maculosa exploits host‐plant volatiles to locate the legume pod borer, Maruca vitrata. Issue 8 (17th August 2018) - Agbessenou, Ayaovi; Tounou, Agbéko Kodjo; Dannon, Elie Ayitondji; Datinon, Benjamin; Agboton, Cyriaque; Ramasamy, Srinivasan; Pittendrigh, Barry Robert; Tamò, Manuele
Abstract: Nemorilla maculosa Meigen (Diptera: Tachinidae) is a solitary endoparasitoid of the legume pod borer, Maruca vitrata Fabricius (Lepidoptera: Crambidae), a key pest of cowpea, Vigna unguiculata (L.) Walp. (Fabaceae) in Africa. A colony of N. maculosa, introduced for experimental purposes from Taiwan to the laboratories of the International Institute of Tropical Agriculture (IITA) in Benin, was used for our studies. Olfactory reponses of N. maculosa to leaves of infested or uninfested cowpea and yellow peabush, Sesbania cannabina (Retz.) Pers. (Fabaceae), and to M. vitrata larvae were evaluated in a four‐arm olfactometer. For all combinations of odor sources, responses between naïve and oviposition‐experienced female flies did not differ. Nemorilla maculosa females were attracted by odors from uninfested leaves of yellow peabush and flowers of cowpea when compared with clean air, and they were attracted to plants damaged by M. vitrata with larvae removed. However, the female fly did not discriminate between odors from infested and uninfested plants. The parasitic fly N. maculosa proved well able to use volatile compounds from various host plants (peabush and cowpea) to locate its host, with a more pronounced attraction by the combination of host larvae and infested host plant parts. These findings are discussed in light of the prospective use of N. maculosa as a biological control agent against the legume pod borer. Abstract : Both naïve and oviposition‐experienced Nemorilla maculosa (Diptera: Tachinidae) parasitoid females were attracted by volatiles from uninfested leaves of Sesbania cannabina and flowers of cowpea when compared with clean air. They were also attracted to plants damaged by Maruca vitrata (Lepidoptera: Crambidae) upon removal of caterpillars. Female parasitoids did not discriminate between volatiles from infested and uninfested plants, but proved well able to use volatile compounds from both host plants (peabush and cowpea) to locate its host.